Phytochemical Profile and Antioxidant Potential of Tobacco Flower Extract in Different Solvents - Wijayanti, Ernanin Dyah; Rahayu, Lina Oktavia; Dzulaikha, Shovia; Ayunda, Fiddini Robetta; Djara, Selfiana (JSMARTech: Journal of Smart Bioprospecting and Technology, 2024)
Tobacco (Nicotiana tabacum) is a commercial plant that is extensively used, particularly for its leaves. Thus far, exploration on the flower part is still limited. The objective of this study was to evaluate the phytochemical profile and antioxidant activity of tobacco flower extracts in different solvents. Tobacco flowers were macerated separately in methanol, ethanol, and n-hexane. Each extract was assayed by color reaction test to detect the phytochemical content. Total phenolic content (TPC) and antioxidant activity were determined by Folin-Ciocalteu and DPPH methods, respectively. Flavonoids, saponins, alkaloids, and triterpenoids are detected in methanol and ethanol extract, anthraquinones is only detected in methanol, while glycosides and steroids are only detected in n-hexane extracts. Among the other extracts, the methanol extract was the richest in phytochemical compounds and had the highest TPC (132.589±0.662 mgGAE/g). However, tobacco flower extract in all solvents were less effective as antioxidant due to very high IC50 values (>500 µg/mL).